Conceptual Confession: Asymmetrical Emotion in Writer-Reader Relations in Trisha Low's The Compleat Purge - Siltanen Elina (Indiana University Press, 2022)
Discussions of American experimental poetry's relation to emotion have been common over the past several years, but few studies have examined the varieties of emotional power in such writing. Moreover, such discussion has viewed conceptually experimental and confessional approaches as incompatible. But Trisha Low's The Compleat Purge (2013) balances itself between conceptualism and confessionalism. It examines emotions like boredom, fascination, and shame as it manipulates relations of form and feeling by engaging affective repetition and emotional excess. Developing a relationship to confessional authenticity that foregrounds emotional vulnerability despite a possible critical distance from the latter, Low's writing suggests that the gap between conceptual and confessional approaches is not as wide as many assume.